Digital libraries: for cultural heritage, knowledge dissemination, and future creation 13th international conference on Asia-Pacific digital libraries, ICADL 2011, Beijing, China, October 24-27, 2011. proceedings - Xing, Chunxiao; Crestani, Fabio; Rauber, Andreas (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 13th International Conference on Asia-Pacific Digital Libraries, ICADL 2011, held in Beijing, China, in October 2011. The 33 revised full papers, 8 short papers and 9 poster papers presented were carefully reviewed and selected from 136 submissions. The topics covered are digital archives and preservation; information mining and extraction; medata, catalogue; distributed repositories and cloud computing; social network and personalized service; mobile services and electronic publishing; multimedia digital libraries; information retrieval; and tools and systems for digital library.